Preparation of coal gangue foam concrete modified by nanomaterials: Physical properties, pore structure, and electromagnetic properties - Qin-Chuan Tu; Qing-Hui Xia; Ying-Hua Bai (Case Studies in Construction Materials, 2024)
In this study, coal gangue foam concrete (CGFC) was modified with nanomaterials to optimize its electromagnetic wave (EWV) absorption performance. Single-factor test was carried out to explore the effects of nano-silica (NS) and nano-calcium carbonate (NC) on the physical characteristics, hydration products and microstructure of CGFC. The results showed that the compressive strength of CGFC was the optimal when NS and NC were mixed with 1.5 wt% each, in which case the volume water absorption also decreased to the lowest value of 20.61 %. Additionally, compared with the control group, the incorporation of NS significantly accelerated the cement hydration rate. Moreover, the synergistic effect after the addition of NC promoted the cement hydration to generate more ettringite and C-S-H gel, and partly reduced the average pore size of CGFC, thereby improving the pore structure. Finally, the attenuation constant of the composite material can reach 187.92, and the reflection loss can reach −35.6 dB, demonstrating its excellent electromagnetic wave absorption ability.